Struktur Perayaan Vigili Paskah dalam Missale Romanum 1970 (2002) : Sebuah Catatan Kritis - Stenly Vianny Pondaag (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2022)
This essay discusses the structure of the Paschal Vigil in Roman Missal m 1970 (2002). The celebration of the Paschal Vigil has a very central place in the liturgy of the Catholic Church. It is regarded as mater omnium sacrarum vigilarium, the mother of all celebrations of holy vigils. However, based on the historical study of the development of Paschal celebrations one can identify the problem of the current structure of Paschal Vigil. This essay aims to explain the problematic point of the structure of the current Paschal Vigil. One of the basic observations is that the Liturgy of the Word shows a combination of two elements that have different functions and meanings in the whole celebration, namely (1) the vigil with the Old Testament readings and (2) the liturgy of the word as one part of the mass. In the celebration of the current Paschal Vigil, the vigil with Old Testament readings is disappeared. The author attempts to propose a personal suggestion for revising the current structure of Paschal Vigil. The author's proposal can be considered as a basic idea for further discussion.